Mass and displacement relationships of tree shakers - Horváth, E. (International Journal of Horticultural Science, 2001)
The degree of mechanically harvested fruit removal by shakers is determined by the displacement pattern, the frequency and the amplitude of shaker mechanism attached to the tree trunk. The displacement pattern is derived from the structural setup of the vibration mechanism, the frequency can easily be adjusted by the rev/min (rpm) of the rotating masses. More problems are arising in determining the dynamics of the tree-shaker system. Among others the amplitude of the attachment point and its components, the effective masses reduced to the attachment point.Recent work gives some new insight into the tree-shaker dynamics including new calculation methods to determine the displacement components and the effective masses reduced to the attachment point. A fully new approach is given to include the vibrating soil mass into the total effective mass. The assumptions are supported and verified by laboratory and field measurements.